Emerging evidence on vouchers and faith-based providers in education : case studies from Africa, Latin America, and Asia - Barrera Osorio, Felipe; Patrinos, Harry Anthony; Wodon, Quentin (Directions in development (Washington, D.C.). Human development., 2009)
While public-private partnerships in education in the United States have received a lot of attention, research on such partnerships elsewhere has been limited--even though such partnerships have been steadily gaining prominence, particularly in developing countries. Aiming to fill this gap, this book presents fresh, technically sound empirical evidence on the effectiveness and cost of various public-private education partnerships from around the world, including voucher programs and faith-based schools. The evidence on the impact in terms of school performance, targeting, and cost of public-priv.